Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

CBSE - X - Mathematics - Three Dimensional Geometry

pls answer

Asked by Pandeyo 31st August 2009, 10:22 PM
Answered by Expert

Answer:

In EDC and ABC

EDC = ABC  (given)

ECD  is common.

By AA corollary

EDC ABC

⇒ED/ AB = CD/ BC ..............(1)

Similarly, EDB BFC

⇒ED/ FC = BD/BC ...............(2)

Adding (1) and (2)

ED/AB + ED/ FC = CD/BC + BD/BC

ED (1/AB + 1/ FC) = 1/BC (CD + BD)

Now on sunbstituting AB=x,ED=y,FC=z

y (1/x + 1/z) = 1/BC (BC)

y (1/x + 1/z) = 1

1/x + 1/z = 1/y

This is the required proof.

Answered by Expert 1st September 2009, 9:12 AM

Rate this answer

  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Report an issue
Your answer has been posted successfully!